AN ANALYSIS OF PROCLITICS AND ENCLITICS IN WEST NIAS LANGUAGE: A MORPHOSYNTACTIC STUDY - Opirman Waruwu (Research on English Language Education, 2025)
This study examined the use of proclitics and enclitics in West Nias language from a morphosyntactic perspective. Using a descriptive qualitative approach supported by elicited linguistic data from native speakers, the analysis demonstrated that cliticization in West Nias was not merely a phonological attachment but also played an essential grammatical role in sentence structure. The results of this study indicated that the types of clitics found in West Nias language consist of proclitics, which attach to the beginning of a host word, and enclitics, which attach to the end of a host word. The proclitic forms identified in this language are a-, i-, ta-, ba-, ö-, u-, la-, and mi-o-, while the enclitic forms identified are -gu, -mö, -ma, -mi, -ra, and -nia. In West Nias, proclitics function as pronominal markers that indicate the actor and primarily attach to verbs, as well as to preverbal elements such as modals and certain prepositions. Enclitics attach to nouns to mark possession, and may also occur on verbs, adjectives, and adverbs when these elements function as the predicate. Therefore, proclitics in West Nias are pronominal because their presence corresponds with the subject of the clause.